Global Education Policies versus local realities. Insights from Uganda and Mexico. Issue 3 (3rd April 2021) - Tromp, Rosanne Elisabeth; Datzberger, Simone
ABSTRACT: National education policies often emerge from the global arena. These global policy norms hold the promise that reforms will produce similar education and development outcomes in different contexts. However, research on how and why global education reforms are practised 'on the ground' and with what effects is still scant. In this paper, we investigate how two global education agendas, namely Universal Primary Education (UPE) and Competency-Based Education (CBE), are enacted and re-contextualised in Uganda and Mexico. By drawing on data obtained from extensive field research in both countries, we explore how these global policies were translated into practice within their situated, professional, material and external contexts. Our research shows that in both cases the enactment of global policies differed widely from universal agendas. We, therefore, argue that global education norms in education can also reproduce existing inequalities or even lead to new forms of inequalities at the local level.